PERINTISAN WIRAUSAHA PIK-REMAJA MUDA JAYA BHAKTI JOYONTAKAN MELALUI PELATIHAN PEMBUATAN ASESORIS INTERIOR DENGAN TEKNIK ECOPRINT - Putri Sekar Hapsari (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
This community service activity aims to form and strive to foster entrepreneurial motivation for economically independent youth groups; productive thinking; and improve the ability of other skills needed to increase income in the future. The training that will be carried out is planned as one of the activities for PIK-Remaja Muda Jaya Bhakti, it is hoped that the development of the Ecoprint startup can support efforts to grow new entrepreneurs which are now needed to increase the entrepreneurial spirit which is still low in the Joyontakan area. Besides this, the Ecoprint training also improves the skills of youth groups which will have an impact on economic benefits by utilizing the potential of nature. Lack of human resource capabilities, lack of insight and lack of equipment causes people to not have this entrepreneurial motivation. The manufacture of interior accessories using the ecoprint technique, which will be pioneered in Joyontakan, is in the form of making interior accessories in the form of cushions, sofa covers, wall panels and decorative lights made from primisima and calico fabrics. Interior accessories using the Ecoprint technique were chosen because apart from an open market share, they also do not require relatively large capital and do not require complex skills for the target community category in the Joyontakan area. The training participants are expected to be able to become strong craftsmen, so that they can increase family income and absorb the workforce of the surrounding community. This activity is planned for a period of six months, the planned activities are; counseling on entrepreneurial potential, training on making Interior Accessories using the Ecoprint technique, namely cushions, sofa covers, wall panels and decorative lights, as well as the use of practical and appropriate tools, then training on the development of designs that are currently in demand by the market.